EVALUASI PENERAPAN PERMENAKER NO. 5 TAHUN 2018 DI PT. XYZ PABRIK PENGOLAHAN PADI DAN JAGUNG CABANG SUMBAWA NUSA TENGGARA BARAT - Tirta, Andy; Haryandi (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
Factors affecting the safety and health of the work environmentprocessing of rice and maize at PT XYZ Sumbawa Branch, West Nusa Tenggara accordinglywith Permennaker No.5 of 2018 are noise, vibration, lighting, temperature andhumidity, wind speed and water. Occupational health and safety is aresponsibility of all workers. A very healthy, nurturing and safe working climatesupport the increase in labor productivity as a human resource. Aimfrom this research is how the K3 program on the activities of PT. XYZ BranchSumbawa, how to work climate factors such as noise, vibration, temperature andhumidity, wind speed, water and lighting referred to in PermenakerNo.5 of 2018 in the work activities of employees and workers at PT. XYZ SumbawaWest Nusa Tenggara, and whether the K3 working climate is in accordance with Permenaker No.5 of 2018has been implemented by PT. XYZ Sumbawa Branch. The research method usedin this research is experimental quantitative. The object of this research is workersPT. XYZ Sumbawa, West Nusa Tenggara. This research data comes from the placeprocessing of corn and grain at PT. XYZ Sumbawa, West Nusa Tenggara. DataThis research is the result data from the vibration test using a vibration meter, testnoise using a sound level tool, using a temperature and humidity metergun and humadity thermometer tool, lighting test using anemometer, testwater using a PH meter and TDS, wind speed test using an air flow toolanemometer. The research data were analyzed descriptively and quantitatively based on the dataquantitative. The results of this study indicate the factors that influence the work climateare noise, vibration, temperature and humidity, wind speed, water and lightingas referred to in Permenaker No.5 of 2018 has no effect onwork activities of employees and workers at PT. XYZ Sumbawa, West Nusa Tenggara.Meanwhile, the work climate of K3 according to Permenaker No.5 of 2018 is not allimplemented by PT. XYZ Sumbawa Branch because there are several working climatesdoes not comply with government standards namely noise (89.5-99.6 dBA) vibration (5.2-5.5 m / s2), and temperature (27oc) and humidity (50-62%) workspace while appropriatewith Permenaker No. 5 of 2018 are lighting, wind speed, and water.